Observations from Working with Female Obsessionals - Patricia Gherovici; Jamieson Webster (EJP import test, 2015)
Summary: This paper is based on observations and speculations derived from the clinical practice of two women psychoanalysts in the United States where they encounter a growing prevalence of female obsessionality. They investigate what might be different about obsessional features in men and women and how this might define differently the direction of the treatment. By way of Joan Riviere, who takes an obsessional woman as the example to develop her notion of womanliness as masquerade, they test how useful the notion of the phallus is in these cases, while problematizing the implied connection between Lacan’s concept of semblance and the clinical direction of the cure.
Keywords: Feminine Psychopathology; Lacan; Masquerade; Obsession; Riviere